The relationship between job burnout and presenteeism among Chinese primary public health physicians: a moderated mediation model - Xinru Kong; Miaomiao Zhao; Ruyu Li; Zhouxiang Li; Danfeng Chang; Xinyi Zhou; Qiang Ma; Yuexia Gao (BMC Medical Education)
Abstract Background Public health physicians are experiencing increased work stress and workload, leading to heightened negative emotions and presenteeism. This study investigates the relationship between job burnout and presenteeism among primary public health physicians in China and explores the potential mediating effect of depressive symptoms, and moderating effects of coping styles and organizational support on these associations. Methods 955 primary public health physicians were surveyed from September to December 2022 in China. Presenteeism was assessed using the Stanford Presenteeism Scale (SPS-6). A moderated mediation model was used to understand the moderating relationship between job burnout (X), depressive symptoms (M) mediated presenteeism (Y), coping styles (W1), and organizational support (W2), controlling for all possible covariates. Results 69.95% of participants showed job burnout in work and 50.16% experienced depressive symptoms, with the average score of presenteeism 16.90 ± 5.74. Job burnout was positively associated with presenteeism score (Effect = 2.23, 95%CI [1.93,2.53]). Mediation analyses revealed that depressive symptoms significantly mediated this relationship (indirect effect = 0.96, 95%CI [0.70,1.25]). Moderated mediation further indicated that the interaction of coping styles and job burnout was negatively related to depressive symptoms, and the interaction of organizational support and depressive symptoms was positively related to presenteeism among public health physicians. Conclusion High job burnout and higher depressive symptoms may contribute to presenteeism. Positive coping styles and appropriate organizational support could buffer the detrimental effects by reducing job burnout and depressive symptoms. Clinical trial number Not applicable.